2013
DOI: 10.1093/nar/gkt576
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of RNA–protein complexes in Escherichia coli and applications to RNA biology

Abstract: RNA has emerged as a major player in many cellular processes. Understanding these processes at the molecular level requires homogeneous RNA samples for structural, biochemical and pharmacological studies. We previously devised a generic approach that allows efficient in vivo expression of recombinant RNA in Escherichia coli. In this work, we have extended this method to RNA/protein co-expression. We have engineered several plasmids that allow overexpression of RNA–protein complexes in E. coli. We have investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 67 publications
1
56
0
Order By: Relevance
“…Indeed, this assay could very well be adapted to any substrate because the RNA scaffold encapsulated in the OprM proteoliposomes can be modified. The RNA scaffold has a restriction site in which any nucleic acid material can be inserted 25 . Furthermore, DNA/RNA aptamers specific for an increasing number of targets are now available, and it has been shown that it is possible to rationally convert non-fluorescent aptamers into fluorescent reporters 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this assay could very well be adapted to any substrate because the RNA scaffold encapsulated in the OprM proteoliposomes can be modified. The RNA scaffold has a restriction site in which any nucleic acid material can be inserted 25 . Furthermore, DNA/RNA aptamers specific for an increasing number of targets are now available, and it has been shown that it is possible to rationally convert non-fluorescent aptamers into fluorescent reporters 26 .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The tRNA-carried ncRNAs include a number of viral RNAs, RNA aptamers, hammerhead riboswitch RNAs, and human pre-miRNAs. [32][33][34][35][36][37][38][39] Nevertheless, levels of recombinant ncRNAs accumulated in cells are largely variable and inevitably dependent upon the structures and metabolic stabilities of chimeric RNAs. 34,35,40 An optimal ncRNA scaffold (OnRS) approach has been developed toward a more general, versatile, and robust high-yield and large-scale production of RNAi agents 40 (Table 1).…”
Section: Bioengineering Of Rnai Agents In Vivomentioning
confidence: 99%
“…With the idea that SmpB may protect aa-tmRNA from degradation, we decided to co-overproduce the A. aeolicus SmpB (aa-SmpB) and aa-tmRNA in LB medium. Both genes were cloned in our homemade plasmid pProRNA (Ponchon et al 2013). RNA transcription is constitutively controlled by the lpp promoter, while that of SmpB is controlled by the inducible lac promoter.…”
Section: Co-overproduction Of Tmrna With Either Smpb or His6-ms2 Coatmentioning
confidence: 99%
“…We recently reported the co-overproduction of the armored version of aa-tmRNA (Ar-aa-mRNA) with the MS2-His6 coat protein (138 aa) using the homemade p44K plasmid (Ponchon et al 2013). The Ar-aa-MLD was modified compared to wild type to incorporate, instead of the short stemloop of the aa-MLD, the 23-nt-long encapsidation signal stem-loop of the MS2 coat protein (Fig.…”
Section: Co-overproduction Of Tmrna With Either Smpb or His6-ms2 Coatmentioning
confidence: 99%
See 1 more Smart Citation